Foreign Entry Modes Under Institutional Pressures: The Impact of Strategic Resource Seeking and Market Seeking Strategies - Ferreira, Manuel Portugal; Serra, Fernando Antônio Ribeiro (Revista de Ciências da Administração, 2008)
Multinational corporations (MNCs) are subject to the various dimensions of the external institutional environments. Institutional theory suggests that MNCs need to conform to the prevailing rules, norms and procedures of the locations where they operate in order to survive and grow. This means that MNCs need to develop the best possible configuration of strategy-structure for their worldwide operations. Previous research has noted that in these conditions firms may simply seek to follow a referent other. However, MNCs’ specific strategy for a focal foreign operation is likely to determine the entry mode for each host country. In certain circumstances it may be whether MNCs are pursuing a market-seeking strategy or a strategic resource seeking strategy that shapes the entry mode in face of the prevailing institutional pressures. We contribute to the understanding of entry modes into foreign markets as a reflection of a strategic choice that is bound by institutional constraints.